Novel Mechanism of Blood Pressure Regulation By Foxo1-Mediated Transcriptional Control of Hepatic Angiotensinogen - Qi, Yajuan (2014)
The renin-angiotensin system (RAS) is a major determinant of blood pressure regulation. It consists of a cascade of enzymatic reactions involving three components: angiotensinogen (Agt), renin, and angiotensin-converting enzyme (ACE), which generate angiotensin II (Ang II) as a biologically active product. Agt is largely produced in the liver, acting as a major determinant of the circulating RAS, which exerts acute hemodynamic effects on blood pressure regulation. How the expression of Agt is regulated is not completely understood. Here we hypothesize that Agt is regulated by forkhead transcription factor forkhead box class O1 (Foxo1), an insulin-suppressed transcription factor, and thereby controls blood pressure in mice. We generated liver-specific Foxo1 knockout mice (L-F1KO mice), which exhibited a reduction in plasma Agt and Ang II levels and a significant decrease in blood pressure. Using hepatocyte cultures, we demonstrated that overexpression of Foxo1 increased Agt expression, while hepatocytes lacking Foxo1 demonstrated a reduction of Agt gene expression and partially impaired insulin inhibition on Agt gene expression. Furthermore, mouse Agt prompter analysis demonstrated that the Agt promoter region contains a functional Foxo1 binding site, which is responsible for both Foxo1 stimulation and insulin suppression on the promoter activity. Together, these data demonstrate that Foxo1 regulates hepatic Agt gene expression and controls plasma Agt and Ang II levels, modulating blood pressure control in mice.